Legal Aspects Of Business Contract Planning In The Digital Era - Jayanti, Atika Putri; Karmenita, Mathilda; Rade, Stefanus Don (Fakultas Hukum Dehasen, 2025)
The advancement of digital technology has significantly transformed the way businesses are conducted, including the drafting of contracts. In the digital era, contracts are not only prepared conventionally but also in electronic forms using digital signatures, online platforms, and blockchain technology. This article discusses the legal aspects relevant to the drafting of digital business contracts, including the validity of electronic contracts, data protection, and dispute resolution. The study refers to the applicable legal frameworks, such as Indonesia’s Electronic Information and Transactions Law (UU ITE) and regulations related to digital contracts. The research shows that although adequate legal foundations exist, challenges persist, particularly regarding the validity of electronic evidence and data security. Therefore, regulatory harmonization and education for business actors are necessary to ensure legal compliance and risk mitigation in the digital era.